Penjatuhan Pidana Ganti Rugi Sebagai Pidana Pokok Dalam Kejahatan Terhadap Harta Benda - Erdianto Effendi (Jurnal USM Law Review)
This study aims to examine and analyze efforts to resolve cases of crimes against property that have been committed by imposing prison sentences that cannot recover losses suffered by victims. Through the restorative justice approach, judges should be given the option to impose criminal compensation on victims as the main crime that has not been regulated in both the Criminal Code and the Criminal Code Bill. The research method used is normative juridical with a statutory, conceptual, and comparative approach. The results of the discussion of this study provide an alternative  to the settlement  or enforcement of crimes against property by proposing the imposition of criminal compensation to victims as the main crime. This concept is different from the application of restorative justice so far in Indonesia or abroad which applies it at the level of investigation and prosecution.